Peran Mediasi Stres Kerja pada Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Perawat di Ruang Perawatan Pasien Covid-19 RSUD Dr. Pirngadi Medan - Dewi Sri Rezeki; Sjahril Effendy Pasaribu; Syaiful Bahri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to determine the mediating role of work stres on the effect of workload and work environment on the performance of nurses in the Covid-19 patient care room at RSUD Dr. Pirngadi Medan in 2021. The research method used is quantitative research, where variables are measured using a Likert scale. The number of samples in this study were 80 nurses in the Covid-19 patient care room at the Dr. Pirngadi Medan. The data collection technique of this research is the study of documents and questionnaires. The data analysis technique in this study used a quantitative approach using statistical analysis using the Outer Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results showed that (1) workload had a significant effect on the performance of nurses in Dr. RSUD. Pirngadi Medan. (2) Directly the work environment has a significant effect on the performance of nurses at RSUD Dr. Pirngadi Medan. (3) Directly work stres has a significant effect on the performance of nurses in RSUD Dr. Pirngadi Medan. (4) Directly workload has a significant effect on work stres on nurses at RSUD Dr. Pirngadi Medan. (5) Directly the work environment has a significant effect on the work environment of nurses at RSUD Dr. Pirngadi Medan. (6) Indirectly the workload has a significant effect on the performance of nurses through work stres at RSUD Dr. Pirngadi Medan. (7) Indirectly the work environment has a significant effect on the performance of nurses through work stres in Dr. RSUD. Pirngadi Medan.